Digitalisasi Laporan Keuangan BUMDes Kayu Bawang - Rahma Yuliani; Rawintan Endas Binti; Sustinah Limarjani; Alfian Misra; Enny Hardy; Nur Astri Sari; Muhammad Yasin (Universitas Lambung Mangkurat, 2021)
BUMDes Kayu Bawang which is located in Gambut, Banjar Regency, South Kalimantan is one of the BUMDes that has received village funds and has initiated several business activities such as duck farming, savings and loan businesses and building blocks. The success of BUMDes Kayu Bawang depends on BUMDes management related to planning, organizing, actualizing, controlling and evaluating (Yuliani, 2017). These five things have not been implemented optimally in the management of BUMDes Kayu Bawang so that the business unit they have started has failed. The failure of the business unit at the Kayu Bawang BUMDes is also related to the transparency and accountability of the financial management of village funds. Where the preparation of financial reports on BUMDes is the main obstacle due to the limited ability of human resources in managing BUMDes. Therefore it is necessary to design an appropriate application, training and assistance in the planning and preparation process of the BUMDes Kayu Bawang financial report. The right technology aplication is needed so that BUMDes Kayu Bawang can compile financial reports in an integrated manner in the context of transparency and accountability. The Ministry of Finance's Guidelines on BUMDes Financial Reports state that reports prepared by BUMDes managers must comply with Financial Accounting Standards.Keywords: BUMDes, Financial Reports, Financial Accounting Standards